PEMANFAATAN SOCIAL MEDIA ANALYTICS PADA INSTAGRAM DALAM PENINGKATAN - Alfajri, Muhamad Fitra; Adhiazni, Viranda; Aini, Qurrotul (Master of Communication Science Program, Universitas Diponegoro, 2019)
Currently Instagram is not only a means of communication and information, but has plagued several sectors, especially marketing. One marketing that often happens on Instagram is sales, advertising, branding, and service. To support marketing activities, it needs to be done not only through conventional or old ways, but also should use social media to better reach all the desired consumers. This study aims to find out the focus on the use of Social Media Analytics tools on Instagram as a medium in increasing marketing effectiveness. This research is qualitative descriptive by using purposive sampling technique. Social Media Analytics that is implemented by Instagram in helping users of business profiles is by providing Insight features in which there are three functions, namely activity, audience and content provided in the form of data visualization. The utilization of the insight feature on Instagram has an important role in helping business users in increasing the effectiveness of marketing their products and services.